2021
DOI: 10.3389/fpsyt.2021.637915
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Mentalization to Reduce Maladaptive Defense in Patients With Mental Disorders

Abstract: Background: There are indications of associations between the ability to mentalize and psychological defense mechanisms. However, only a few studies have focused on these associations, and even fewer have included empirical analyses. In the present study, we aimed to fill this research gap by analyzing the link between the ability to mentalize and psychological defense mechanisms in patients with mental disorders. We examined whether changes in defense mechanisms are predicted by an increase in mentalization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 67 publications
(105 reference statements)
0
14
0
Order By: Relevance
“…Such people experience increased anxiety and concern and feel like they are no longer in control of their own lives. Previous studies show that mentalization improves mental health condition and reduces maladaptive defense mechanisms, which may explain the relationship between better-developed mentalization ability and also stress reduction in chronically ill patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such people experience increased anxiety and concern and feel like they are no longer in control of their own lives. Previous studies show that mentalization improves mental health condition and reduces maladaptive defense mechanisms, which may explain the relationship between better-developed mentalization ability and also stress reduction in chronically ill patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic experiences can provoke a decrease in overall defensive functioning and increase the use of mental inhibition defense mechanisms, also called neurotic defenses. Individuals who have experience trauma tend to use defense mechanisms as repression, dissociation, and isolation of affects in order to protect themselves from the awareness of stressful experience that they cannot fully manage [ 46 , 47 ]; this allows them to maintain emotional distance from feeling or ideas associated with the stressor. High-adaptive defense mechanisms, also called mature defenses, moderate the individual’s adjustment to stressful conditions and foster resilience [ 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bond reviewed the published studies about the relationships of defense styles with psychopathology and change and proposed that defense styles should become more adaptive with improvement in symptoms, but intermediate defenses tended to become stable over time ( 19 ). Recently, Hayden et al also demonstrated that maladaptive defense mechanisms were significantly reduced during inpatient therapy and remained low until follow-up, whereas neurotic (intermediate) and adaptive defense mechanisms did not change significantly ( 5 ). In other words, intermediate defenses have been found to be a trait-like factor among the three defense factors.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological defense mechanisms represent a crucial component of individual capacity to maintain emotional homeostasis. Without them the conscious mind would be much more vulnerable to negatively charged emotional input, such as that pertaining to anxiety and sadness ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%